Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1063/1.356544
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-size effects on the band edge of CdTe clusters in glass

Abstract: The measurement of quantum-size behavior in semiconductor crystals has been examined through an analysis of the size dependence of the semiconductor’s absorption edge. In past studies, there appeared to be little agreement between theory and experiment for very small crystals. In this paper, the effects of crystal-size distribution and tunneling of the carrier wave functions into the quantum well barrier are considered. An analysis of the microstructure size and absorption edge of CdTe clusters in a glass matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…The behavior in three dimensions is in agreement with the results in Fig. 2 [12]. We now compare the results in Fig.…”
Section: Validity Of Particle In a Box Model To Determine The Averagesupporting
confidence: 87%
“…The behavior in three dimensions is in agreement with the results in Fig. 2 [12]. We now compare the results in Fig.…”
Section: Validity Of Particle In a Box Model To Determine The Averagesupporting
confidence: 87%
“…1 -7 Although a prediction about the potential of nanotechnology was made as early as 1959, 8 the technological applications grew only when some understanding of the fundamental properties of the materials as a function of grain/particle size evolved during the 1980s and the 1990s. Nanostructured materials are generally synthesized in a number of forms: as isolated or loosely connected nanoparticles in the form of powder, 9 as composites of nanoparticles dispersed in a host, 10 or as a compact collection of nano-grains as pellets 11 or thin films. 12 Though in principle one can define a nanostructured Ł Correspondence to: Akhilesh K. Arora, Materials Science Division, Indira Gandhi Centre for Atomic Research, Kalpakkam 603102, India.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the fundamental issues, we have observed changes in bandgap energy with cluster size which do not adhere to conventional models at small crystal sizes [1] and appear to depend strongly on whether the semiconductor is a 2-6 direct-gap type or a column 4 indirect-gap type. Here, we have observed that composites doped with CdTe, CdS and CdSe in a silica matrix exhibit a pronounced saturation of the predicted blue shift in bandgap energy with decreasing size [2].…”
Section: Introductionmentioning
confidence: 96%
“…Materials science issues involved fabrication processes which lead to a variety of cluster sizes and size distributions [1], and interface structures. Potential applications range from very highly efficient solar cells [6] to fast optical switches.…”
Section: Introductionmentioning
confidence: 99%